2018
DOI: 10.1021/acschembio.8b00389
|View full text |Cite
|
Sign up to set email alerts
|

NCI Program for Natural Product Discovery: A Publicly-Accessible Library of Natural Product Fractions for High-Throughput Screening

Abstract: The US National Cancer Institute's (NCI) Natural Product Repository is one of the world's largest, most diverse collections of natural products containing over 230,000 unique extracts derived from plant, marine, and microbial organisms that have been collected from biodiverse regions throughout the world. Importantly, this national resource is available to the research community for the screening of extracts and the isolation of bioactive natural products. However, despite the success of natural products in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 80 publications
1
101
0
1
Order By: Relevance
“…To our knowledge this is also the case for the National Chinese Compound Library in Shanghai, China (http://en.cncl.org.cn/). Finally, national or transnational efforts have been reported to create such depositories of compounds for the use of screening programs from the Academy: see Horvath et al (2014) in Europe and Thornburg et al (2018) for the NIH/NCI effort. In addition, vendors are also selling libraries of compounds composed of a "large" diversity that they build according to different principles (Boss et al, 2017).…”
Section: Screening For New Drugs and Discovery Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge this is also the case for the National Chinese Compound Library in Shanghai, China (http://en.cncl.org.cn/). Finally, national or transnational efforts have been reported to create such depositories of compounds for the use of screening programs from the Academy: see Horvath et al (2014) in Europe and Thornburg et al (2018) for the NIH/NCI effort. In addition, vendors are also selling libraries of compounds composed of a "large" diversity that they build according to different principles (Boss et al, 2017).…”
Section: Screening For New Drugs and Discovery Approachesmentioning
confidence: 99%
“…Indeed, robots can handle several thousands of tests during a workday. However, the initial enthusiasm for HTS (Harvey and Cree, 2010;Sarker and Nahar, 2012) when applied to crude extract libraries in targeted assays systems has been facing several issues as stated recently by Thornburg et al (2018). In fact, HTS techniques do not really modify the discovery process itself.…”
Section: Strategies For Identification Of Bioactive Compounds From Crmentioning
confidence: 99%
“…[130] Therefore, the isolation of naturale xtracts,t heir screening, and further identification of active components still remain important strategies of drug discovery. [131] Analysis of new drugs entering the market, according to their registration year (1981-2010) and origin (i.e.,s ynthetic, natural, or modified NP), showed that the number of drugs comingf rom natural sources decreased, to al esser extent, over thesey ears comparedw ith fully synthetic compounds ( Figure 27). [132] More detaileda nalysis of approved drugs based on NPs showed that, initially,t hey originated only from plants.…”
Section: Role Of Nps In Drug Discoverymentioning
confidence: 99%
“…Natural product extracts are complex mixtures of compounds of unknown molecular weight with variable polarity, solubility and stability, which also may contain colored compounds, uorophores or toxins that can cause assay interference and liquid handling problems in many modern HTS platforms. 23 Consequently, various academic, government and industry groups have incorporated chromatographic separation techniques such as solid phase extraction (SPE), [24][25][26][27][28][29] counter-current chromatography (CCR), 30,31 high performance liquid chromatography (HPLC), [32][33][34][35][36][37] or supercritical uid chromatography (SFC) 38,39 to partially purify components of an extract prior to assay (i.e. prefractionation).…”
Section: Natural Product Libraries For High-throughput Screeningmentioning
confidence: 99%
“…Partial purication by prefractionation and increased automation of subsequent purication efforts can also streamline this process. 26,108 Conversely, cell-based assays also complement biochemical HTS. For example, a cell-free protein-protein interaction assay was developed to screen for substances able to disrupt the binding interaction between HIF1a and the transcriptional coactivator P300.…”
Section: Active Sample Prioritizationmentioning
confidence: 99%